Obstáculos epistemológicos : implicações na aprendizagem do conceito de átomo - Reis, Jheniffer Micheline Cortez dos (2015)
Current research analyzes the teaching conditions and identifies in Chemistry Course undergraduates the possible epistemological obstacles related to the concept of the atom and its implications on the learning of further chemical knowledge. Gaston Bachelard´s notion on epistemological obstacle was employed as a reference in search of the following questions: Do Chemistry undergraduates present any epistemological obstacles with regard to the understanding of the atomic model? How do these obstacles interfere in the learning of concepts on chemical bonds and in the interpretation of phenomena related to this knowledge? The qualitative research was conducted with students during a series of lessons on General Chemistry during the first year of the Chemistry Course in a government-run university in the state of Paraná, Brazil. Data collected by questionnaires, formal assessment of the discipline, diary reports and recordings of all instances of the lessons were relevant for current research. So that the analysis and interpretation of results could be composed, data were treated according to Bardin´s content analysis and discussed, with Bachelard as reference. One could identify that some students have realistic concepts on the atom, as a small and indivisible particle. Further, the verbal obstacle was identified in the analogies and metaphors for the explication of the concept of the atom, which may affect an abstract vision of the atom. It may be underscored that substantialism is one of the most important impairments for the understanding of current atom model. When the influence of obstacles in the understanding of the phenomenon with regard to the burning of magnesium is analyzed, one could identify the first experience associated with realism and that which could be only macroscopically observed. In fact, the greatest challenge in the teaching of Chemistry is the development of an idea at the atomic level and, within the same process, a disruption between common sense knowledge and scientific knowledge. Results reveal the necessity and importance of knowing and overcoming the epistemological and pedagogical obstacles in the teaching and learning process of chemical concepts.